The effect of microwave processing and use of antimicrobial agent on porosity of conventional heat cured denture base resin: An in vitro study - U K Kartika; Benaiffer Agrawal; Naveen S Yadav; Praval Pratap Singh; Tripty Rahangdale (Wolters Kluwer Medknow Publications, 2015)
Statement of Problem: The occurrence porosity in polymethyl methacrylate, the most commonly used denture base material is a problem. The occurrence of oral candidiasis and other infections has also been reported in denture users. Purpose: The aim of this study was to evaluate the effect of addition of an antimicrobial agent, silver zeolite on the porosity of denture base resin, which will be an effective tool in the prevention of oral candidiasis among denture wearers. This study also aims to analyze the effect of polymerization technique on porosity in zeolite incorporated dentures to develop a denture base resin which will be easy to process with optimal mechanical and antimicrobial properties. Materials and Methods: Eighty rectangular resin specimens (65 mm × 40 mm × 5 mm) were divided into one control group (A) and three experimental groups (B - Microwave cured denture base resin specimens, C - Conventionally cured denture base resin incorporated with antibacterial zeolites, D - Microwave cured denture base resin incorporated with antibacterial zeolites) porosity was calculated by measurement of the specimen volume before and after its immersion in water. Data were analyzed using one-way analysis of variance. Results: The mean values of the percent mean porosity were: A = 0.9555%, B = 0.9590%, C = 0.9630%, D = 0.9695%. No significant differences were found in mean porosity among the groups evaluated. Conclusion: Within the limitations of this study, it could be concluded that the addition of zeolites did not result in significant porosity and that the use of microwave processing is a viable option for denture processing.